Urea Berlapis Bakteri untuk Mengurangi Dosis Pupuk Urea pada Budidaya Kentang - Hindersah, Reginawanti; Suryatmana, Pujawati; Fitriatin, Betty Natalie; Asmiran, Priyanka; Nurbaity, Anne; Setiawati, Mieke Richimi (Jurnal Penelitian Pertanian Terapan, 2024)
Urea fertilizers and biofertilizers play an important role in potato (Solanum tuberosum L.) cultivation, but urea fertilizers are volatile and leach out easily that reduce their effectiveness. Urea coated with beneficial bacteria-enriched organic matter is expected to increase nitrogen used efficiency. The purpose of the experiment was to determine the ability of bacterial-coated urea (BCU) included Bacillus and Azotobacter to improve the growth, nutrient status and yields of potatoes grown in field; as well as to reduce urea dose. The experiment was setup in randomized block design with five treatments and six replications. The treatments were four combinations of the dose and formulation of BCU; and conventional urea fertilizer as control treatment. Application of both BCU formulation increased plant height as well as N and P uptake particularly when the recommended dose was used.  In contrast, the doses and formulation of BCU did not affect chlorophyll content. Application of BCU-A or BCU-B at the rate of 200 kg/ha increased tuber weight by 59% and 81% respectively.  Both high and low dose of BCU did not reduce the vegetative growth and yield compared to the plants fertilized with conventional urea. This experiment showed that BCU is considered to reduce the rate of Urea in potatoes cultivation.